2015
DOI: 10.1186/s12879-015-1082-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standard dose multivitamin supplementation on disease progression in HIV-infected adults initiating HAART: a randomized double blind placebo-controlled trial in Uganda

Abstract: BackgroundEfficacy trials investigating the effect of multivitamin (MV) supplementations among patients on Highly Active Antiretroviral Therapy (HAART) have so far been inconclusive. We conducted a randomized, double blind, placebo controlled trial to determine the effect of one recommended daily allowance (RDA) of MV supplementation on disease progression in patients initiating HAART.MethodsEligible subjects were randomized to receive placebo or MV supplementation including vitamins B-complex, C and E. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 27 publications
1
29
1
Order By: Relevance
“…Of the new included trials, four reported outcome data in two articles ( Asdamongkol 2013 THA ; Bang 2012 DEN ; Baum 2010 USA ; Baum 2013 BWA ), and two letters of correspondence were related to one included trial ( Isanaka 2012 TZA ). Two included trials published their trial protocols ( Guwatudde 2015 UG ; Kamwesiga 2015 RWA ). We identified one additional trial from our most recent search (18 November 2016), which we included in the ' Characteristics of studies awaiting classification ' section.…”
Section: Resultsmentioning
confidence: 99%
“…Of the new included trials, four reported outcome data in two articles ( Asdamongkol 2013 THA ; Bang 2012 DEN ; Baum 2010 USA ; Baum 2013 BWA ), and two letters of correspondence were related to one included trial ( Isanaka 2012 TZA ). Two included trials published their trial protocols ( Guwatudde 2015 UG ; Kamwesiga 2015 RWA ). We identified one additional trial from our most recent search (18 November 2016), which we included in the ' Characteristics of studies awaiting classification ' section.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized trial conducted among 40 HIV-infected adults on ART in the US found multivitamin and mineral supplements improved CD4 T-cell counts after 3 months as compared with placebo [13]. In contrast, a recent trial of 400 HIV-infected Ugandan adults initiating ART found no effect of single RDA supplements containing vitamins B, C, and E on CD4 T-cell counts up to 18 months [12].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the consistent evidence base for ART-naïve patients, randomized trials of multivitamins for ART-experienced patients have determined mixed results on CD4 T-cell reconstitution and other immunological markers [12][13][14][15][16]. A randomized trial conducted among 40 HIV-infected adults on ART in the US found multivitamin and mineral supplements improved CD4 T-cell counts after 3 months as compared with placebo [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrolling patients who initiated ART less than six months ago, a randomized double-blind placebo-controlled trial in Uganda investigated the effect of a multivitamin supplement on immune reconstitution, weight gain, and quality of life of ART patients [ 51 ]. The trial found no significant impact from the multivitamin on any of its three primary endpoints [ 52 ]. In addition, there is evidence of possible harm from high-dose multivitamin supplements in patients on ART with a randomized trial, comparing standard-dose to high-dose multivitamin supplementation in Dar es Salaam, having been stopped early due to an increased risk of raised alanine transaminase levels in the high-dose multivitamin group [ 53 ].…”
Section: Discussionmentioning
confidence: 99%